Estado nutricional de niños en edad preescolar del barrio Shucos de la ciudad de Loja, y su relación con los hábitos alimentarios y actividad física en el periodo junio-septiembre del 2015. - Celi Soto, Henry Leonardo (2017)
Nutritional status is the situation in which a person is in relation to the intake and physiological adaptations that take place after the nutrient intake. The objective of this research was to determine the nutritional status of preschool children in the Shucos neighborhood of the city of Loja and their relationship with eating habits and physical activity in the period June-September 2015. To do this, Carried out a descriptive, quantitative, relational and transverse cohort investigation in the Shucos neighborhood of Loja canton, constituting a sample of 62 children, from whom weight was taken, and with this, the IMC was obtained, in addition to the form Data collection Krece-plus test, statistical analysis was performed through the software Microsoft Excel 2010 and SPSS. It was obtained with normal nutritional status 53.2%, overweight was also found with 16.1%, in addition to obesity and mild malnutrition with 11.3% each, and last severe malnutrition, with 8, 1%. Most of them presented a normal nutritional status and according to the Krece-plus test with high nutritional level, overweight with very low nutritional level, obesity with a very low nutritional level, malnutrition with very low nutritional level, and malnutrition Severe according to the Krece-plus test with a very low nutritional level. Likewise, we found preschoolers who had normal nutritional status and according to the Krece-plus test with good physical activity level, overweight with poor physical activity level, obesity with poor physical activity level, malnutrition with regular physical activity level, and Severe malnutrition according to the Krece-plus test with level of regular physical activity. The conclusions that were identified were the strong relationship of nutritional status with eating habits, and finally with physical activity but in weak relation. Keywords: Nutritional status, physical activity, eating habits